Analysis and design of networked control systems - Saba Salehi (2009)
In Networked Control Systems (NCSs), the communication between different components, is established through a shared digital network. This kind of communication, results in problems such as network induced transmission delays, packet losses, bandwidth limitations, multiple packet transmission, etc., which may affect the performance of the system or even lead to instability. Therefore, in designing controller for such systems these unfavorable effects should be taken into consideration. In this thesis, the focus is on control over networked systems with time delays or packet dropouts. Our goal is to first model NCSs with delays and packet dropouts, develop tools for stability analysis and control synthesis, and then validate the results through numerical examples and simulations and/or practical systems implementation. First, NCSs with two separate uncertain time varying delays in sensor and controller channels are investigated. Uncertainties of the networked control system will be characterized by polytopic uncertain parameters using Jordan canonical form. Markov jump linear systems are then applied to model the time delay of the sensor channel. Control synthesis of the system is considered by using a Lyapunov-Krasovskii approach, and a mode-dependent static output feedback controller is designed which changes for each different subinterval of delays. The results are given in the form of Nanyang Technological University vii Bilinear Matrix Inequalities (BMIs) which can be solved using methods and algorithms available in the literature. Subsequently, through some condition on output matrix, Linear Matrix Inequalities (LMIs) are derived for static output feedback controller. Further extensions for state feedback and dynamic output feedback controllers design are presented as well.